Quest for the Tree Kangaroo : An Expedition to the Cloud Forest of New Guinea - Montgomery, Sy. (Boston Houghton Mifflin, 2006)
Follow a group of explorers and scientists as they travel to Papua New Guinea to find a type of kangaroo that lives in trees.
Primary
Keywords: 1.Matschie's tree kangaroo; 2. Tree kangaroo